OPTIMIZATION OF INVESTIGATIONS BY SATRESKRIM POLRES KLATEN FOR DISCLOSURE OF CURANMOR CRIMINAL CASES IN ORDER TO REALIZE PRECISE LAW - Yoga Nanda Pratama (Police Studies Review, 2022)
This research is based on the low crime clearance condition of Satreskrim Polres Klaten. This is evidenced by the case resolution report obtained from 2019-2021. In the 2019-2021 case resolution report, crime clearance crimes handled by the Klaten Police Station are generally in good condition, but especially in curanmor crimes, crime clearance has decreased every year and is in a very low condition. The author conducts research on the investigation of the curanmor crime with a qualitative research approach with descriptive types of research. There are two formulations of problems that will be the focus of research, including on the implementation of curanmor criminal investigations and about the competencies possessed by Klaten Police Satreskrim personnel. This method of collecting research data through interviews, observations, and document studies by validating data through engineering triangulation, source triangulation, and time triangulation. To analyze the problems in this study used several concepts and theories to analyze problems that have been formulated before. The concept used is the concept of investigation according to Perkabareskrim No. 1-4 of 2014 concerning SOP Criminal Investigation, and Precision Concept. While the theory used is Management Theory, Competency Theory, and SWOT Analysis Theory. The results found include the still not optimal implementation of curanmor criminal investigations and still not optimal competence possessed by personnel of satreskrim klaten police. Therefore, the author formulated several problem solving of the problems faced in a way and innovation formulated to optimize the implementation of curanmor criminal investigations and competencies possessed by Klaten Police Satreskrim personnel so that curanmor crimes can be revealed and crime clearance can be increased so that precise law enforcement can be realized.